Efficient secure system of data in cloud using steganography based cryptosystem with FSN. (2018) - Shanthi, S.; Kannan, R.Jagadeesh; Santhi, S.
Abstract: Data sharing is one of the most important functionality in cloud and one of the challenging problem is sharing data securely with others. Sharing the data with security and confidentiality on cloud with data integrity is discussed in this paper. We describe random key generation algorithm using that random sized public/master-secret key pair is created by data owner. The novelty is that data owner encrypts the data using feistal structure network along with the public key and the data index into an image and this is done by using steganography & then the data are uploaded in the Cloud Server. Aggregate Decryption Key (ADK) is mainly used to generate the Master- secret key where it is used for sharing the data to other users by transferring its ADK to those who are interested in accessing the contents through E-mail by the data owner. Original Data is downloaded only after Verification of ADK and the authentication that are done by 3D scan of finger print authentication.